2019
DOI: 10.26578/jrti.v13i2.5577
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Aktivasi secara Kimia menggunakan Larutan Asam dan Basa terhadap Karakteristik Zeolit Alam

Abstract: Zeolit alam merupakan batuan mineral yang banyak terdapat di Indonesia. Zeolit alam merupakan kristal alumino silikat yang memiliki banyak kegunaan dalam bidang industri, agrikultura, dan pengolahan air limbah. Salah satu proses untuk meningkatkan kualitas dari zeolit alam adalah melalui proses aktivasi. Tujuan penelitian ini adalah melihat pengaruh aktivasi secara kimia menggunakan larutan asam klorida dan natrium hidroksida sehingga mampu meningkatkan aktivitas dari zeolit alam tersebut. Aktivasi zeolit alam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
0
8
0
5
Order By: Relevance
“…Characterization of Acid-activated and Calcined Zeolite Natural zeolite was activated by 3 M HCl to remove any organic and inorganic impurities from natural zeolite such as iron, sulfur or phosphorous, cleanse the pores, and leading to decationization-dealumination process of zeolite framework without destroying it (Al Muttaqii et al, 2019;Kadirbekov et al, 2017). The purpose of dealumination is to optimize selectivity, acidity control, and stability at high temperature of natural zeolite (Al Muttaqii et al, 2019). The acid-activated zeolite was characterized by XRD shown in Figure 3.…”
Section: Characterization Of Natural Zeolitementioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of Acid-activated and Calcined Zeolite Natural zeolite was activated by 3 M HCl to remove any organic and inorganic impurities from natural zeolite such as iron, sulfur or phosphorous, cleanse the pores, and leading to decationization-dealumination process of zeolite framework without destroying it (Al Muttaqii et al, 2019;Kadirbekov et al, 2017). The purpose of dealumination is to optimize selectivity, acidity control, and stability at high temperature of natural zeolite (Al Muttaqii et al, 2019). The acid-activated zeolite was characterized by XRD shown in Figure 3.…”
Section: Characterization Of Natural Zeolitementioning
confidence: 99%
“…Quartz phase has been removed by the acid activation process. High concentration of HCl (3 M) and duration of stirring (5 h) could be determining factor for the removal of quartz, because Muttaqii et al, (2019) used HCl concentration less than 3 M and only 2 hours stiring duration, and still observed the present of quartz in acidactivated zeolite. The using of HCl 3 M was also good in decationization of zeolite as what was reported by Tišler et al, (2019) that they observed the increasing in the silicate modulus parameter which indicated that Na and K were rapidly leached from the zeolite so the acid activation process promotes the removal of most of sodium and potassium (Tišler et al, 2019).…”
Section: Characterization Of Natural Zeolitementioning
confidence: 99%
“…Natural zeolite from Sukabumi has three mineral compositions, namely quartz, mordenite, and clinoptilolite, but tends to be mordenite zeolite [26,30]. Malang natural zeolite and Gunung Kidul natural zeolite have a mordenite structure [31]. Zeolite from Wonosari Gunung Kidul is a type of modernite and clinoptilolite with a SiO2 content of 65.56% and Al2O3 of 11.04% [32].…”
Section: Natural Zeolite and Synthetic Zeolitementioning
confidence: 99%
“…This treatment could increase the capacity of porous and surface area for adsorption. Chemical treatment using acid or basic had a function to open the porous, remove the purityy, and rearrange the exchanged atom (Al Muttaqii et al, 2019). The addition of acidic solution into SiO2 also could increase the hydrophobicity of SiO2 that occurs the decreasing of water adsorption (Lu et al, 2009).…”
Section: Activation Of Silica Sorbentmentioning
confidence: 99%